Plasma N-Acetylaspartate Is Related to Age, Obesity, and Glucose Metabolism: Effects of Antidiabetic Treatment and Bariatric Surgery - Daniele, Giuseppe; Campi, Beatrice; Saba, Alessandro; Codini, Simone; Ciccarone, Annamaria; Giusti, Laura; Del Prato, Stefano; Esterline, Russel L.; Ferrannini, Ele (Frontiers in Endocrinology, 2020)
Background: N-acetylaspartate (NAA) is synthesized only by neurons and is involved in neuronal metabolism and axonal myelination. NAA is the strongest signal on brain magnetic resonance spectroscopy, and its concentration have been associated with cognitive dysfunction in neurodegenerative diseases, obesity and type 2 diabetes (T2D). Materials and Methods: We explored the impact of obesity and T2D on circulating NAA as well as the impact of bariatric surgery and antidiabetic treatments. We developed an LC-MS method for the accurate measurements of fasting plasma NAA levels in 505 subjects (156 subjects with normal glucose tolerance, 24 subjects with impaired glucose tolerance, and 325 patients with T2D) to examine the associations of NAA with obesity and dysglycemia. To validate cross-sectional findings, plasma NAA was measured 6 months after Roux-en-Y Gastric Bypass (RYGB) in 55 morbidly obese subjects, and after 1 year of antidiabetic treatment (with dapagliflozin, exenatide or dapagliflozin plus exenatide) in 192 T2D patients. Results: In the whole population, NAA was associated with age (r=0.31, p<0.0001) and BMI (r=-0.20, p<0.0001). Independently of age and BMI, NAA was reciprocally related to HbA1c and fasting plasma glucose (partial r=-0.13, both p=0.01). Surgically-induced weight loss raised NAA (by 18 nmol/L on average, p<0.02). Glucose lowering treatment increased NAA in proportion to the drop in HbA1c (r=0.31, p<0.0001) regardless of the agent used. Conclusions: Circulating NAA concentrations are modulated by age, obesity and glycemic control. Whether they may mark for the corresponding metabolic effects on brain function remains to be established by joint measurements of spectroscopic signal and cognitive function.